Armor Layer Uniformity and Thickness in Stationary Conditions with Steady Uniform Flow - Cahyono Ikhsan; Ariva S. Permana; Arlendenovega S. Negara (Salehan Institute of Higher Education, 2022)
The continuous movement of riverbed particles due to turbulent flow determines the stability of non-cohesive riverbeds and banks during riverbed and bank erosion and sedimentation. This study emulated the stable channel design by deriving the low maintenance cost of the channel through bed protection by an armor layer. The study investigated the effects of shear stress and grain size uniformity to determine the minimum non-cohesive armor layer thickness for the stability of riverbeds under steady uniform flow conditions. Experiments were conducted with four different discharges, five armor material gradations, and five bed-slope variations in a full-scale flume. We observed and recorded the behaviors of the five gradations of armor materials for given discharges and bed slopes. Eighty data points were recorded and analyzed. The hydraulic analysis of the flow along with the soil mechanics analysis of the armor materials was done. The soil mechanic analysis was particularly focused on the uniformity coefficient of the armor layer, Cu, to derive the armor layer equation. However, for the manageability of the study, we set the limit of the Cu between 3.0 and 6.0. From the viewpoint of non-erodibility, a wider Cu value indicated a thinner armor layer. Variables that govern the armor layer thickness and the layer thickness itself were derived and proposed. The variables, namely Cu, shear stress (t0 and tc), and mean diameter of the bed load and armor materials (Db50 and Da50). Our results show that these variables governed the thickness of the armor layer, and this is expected to contribute to the design of stable natural channels, which can minimize the cost of irrigation canal maintenance and development. Doi: 10.28991/CEJ-2022-08-06-01 Full Text: PDF